Linking quality assurance to human resource management: a study of SMEs in Malaysia - Hassan, Arif (Emerald Group Publishing Limited, 2010)
Purpose – As organizations try to provide quality assurance from ISO certification, the importance of people management through better HR management assumes greater significance. This paper aims to examine this issue. It seeks to compare selected ISO certified SMEs with non-ISO certified SMEs on several HR practices. Design/methodology/approach – A sample of 292 employees drawn from ten SMEs, five of them ISO certified, responded to a questionnaire which measured the adequacy of the following HRM systems: career system (manpower planning and recruitment, potential assessment, career planning), work system (role analysis, contextual analysis, performance appraisal), development system (training and learning, performance guidance, knowledge sharing, other means of competency development), self-renewal system (role efficacy, OD practices, action-oriented research), and HRD system (HRD climate, organizational values, quality orientation, reward and recognition). Findings – The results indicated a moderate rating for most of the HRM systems in all the organizations including those with ISO certifications. However, ISO certified companies were perceived to be doing better on managing career system, conducting contextual analysis for goal setting and quality orientation. In the rest of the cases the differences were not significant. Practical implications – The findings suggest that organizations need to go beyond quality assurance to organization-wide quality management through improvement in HR systems and practices. Originality/value – The paper provides empirical knowledge on HR systems and practices and the relationship of these factors with organizational quest for quality in a developing economy.